Оценка экологического риска последствий чрезвычайных ситуаций - Levkevich, Виктор; Kasperov, Георгий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
Methodological base for risk determination and emergency damage evaluation is described. Structure of geographic information system that provides prevention of emergency situations is shown.